Obviating the mood, but mostly under control: Spanish heritage speakers' acquisition of the binding constraints of desiderative complements - Perez-Cortes, Silvia (Language acquisition, 2025)
Verbal morphology has been identified as a particularly vulnerable domain for adult heritage speakers (HSs) of Spanish, especially when it involves the selection of subjunctive mood. A minimal amount is known, however, about the potential effects of the variability associated with these forms on the acquisition of related epiphenomena, such as the anaphoric relations and binding constraints of complements that select subjunctive. The present investigation addresses this gap in the research by focusing on how HSs express and interpret subject co-referentiality and disjoint reference in desiderative constructions. Results from two experimental tasks (a Truth-Value judgment and a Sentence Completion task) revealed that participants' Spanish proficiency was a significant predictor of their performance. In particular, more advanced HSs exhibited a higher likelihood of linking the presence of subjunctive to subject disjoint reference (a pattern observed among most Spanish controls) and a higher probability of using this form to express subject disjoint-reference in production. Furthermore, optionality in this domain was significantly linked to the degree to which HSs restructured the referential properties associated with subjunctive complements. Specifically, participants who exhibited lower rates of structural and morphological variability in connection to the expression of disjoint-reference also appeared to be more likely to assign this reading to the null subjects of subjunctive complements and reject the possibility of subject co-referentiality. These findings provide new evidence of how syntactic dependencies such as subject obviation and control are developed among heritage speakers of Spanish and explore the potential role of structural and morphological optionality in their (re)-configuration.